ARTIFICIAL INTELLIGENCE, BIG DATA ANALYTICS, TIME PRESSURE, AND AUDIT QUALITY: THE MODERATING ROLE OF ETHICAL CULTURE IN PUBLIC ACCOUNTING FIRMS - Ristavia Purwanda; Indah Anisykurlillah (Universitas Riau, 2026)
The rapid advancement of digital technologies has transformed audit practices, creating opportunities and challenges for maintaining audit quality. Drawing on the Theory of Planned Behavior, this study investigates the effects of Artificial Intelligence (AI), Big Data Analytics (BDA), and Time Pressure on audit quality, while examining the moderating role of Ethical Culture. Using a quantitative approach, questionnaire data were collected from 99 external auditors across 25 Public Accounting Firms in Semarang, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that AI and Time Pressure significantly improve audit quality, whereas BDA has no significant effect. Ethical Culture weakens the relationship between Time Pressure and audit quality but does not moderate the effects of AI or BDA. These findings extend the Theory of Planned Behavior by demonstrating that organizational ethical conditions influence how auditors respond to time constraints in technology-enabled audit environments. Practically, the study highlights the need to strengthen ethical culture, organizational readiness, and auditors' digital capabilities to optimize technology adoption and sustain audit quality.